Esneyebilir bir protez kaide rezin ile hareketli bölümlü protezlerin yapımı: vaka sunumu - Ayse Demir; Giray Bolayir; Hakan Demir; Koray Soygun (Cumhuriyet Dental Journal, 2011)
Aesthetic considerations in dental treatment are directly related to the sentiments and opinions of the patient. Aesthetics has been a crucial factor for fixed rehabilitations, but nowadays removable partial dentures also show great interest in satisfying the aesthetic requirements. Tooth selection, teeth arrangement, and the compatibility of the artificial tooth with face structure are known to affect aesthetics in removable partial dentures. In addition to these, poor design of clasp systems can be the major impairment factors in structural components of these dentures. Although development of precision attachments, and the clasp systems, it is unable to obtain satisfying aesthetic with removable partial dentures. In this study, we present a case report that describes the rehabilitation of a patient with a polyamide (PA6.6) denture base resin in order to remedy both the functional and aesthetic considerations.   ÖZET Diş hekimliğinde estetik gereksinimler hastaların duygu ve düşünceleriyle direk ilgilidir. Estetik yaklaşımlar protetik tedavide özellikle sabit rehabilitasyonlar için öncelik taşısa da bugün hareketli bölümlü protezler için de aynı derecede önem oluşturmaktadır. Hareketli bölümlü protezlerde estetin sağlanmasında diş seçimi, diş dizimi, yapay dişlerin yüz şekliyle uygunluğu gibi faktörlerin etkili olduğu bilinmektedir. Bununla birlikte bu protezlerin yapısal unsurları arasında estetiği olumsuz yönde etkileyen en önemlisi kroşe sistemleridir. Estetik gereksinimleri karşılaması açısından birçok kroşe sistemi, hassas tutucular geliştirilmesine karşın bazı vakalarda bu sistemler yeterli olamamaktadır. Bu çalışmada fonksiyonel ve estetik gereksinimleri karşılamak amacıyla geliştirilmiş poliamid (PA 6.6) protez kaide rezin ile yapılan vakamızı sunmayı amaçladık. Anahtar Kelimeler: Hareketli bölümlü protez, estetik, kroşe, poliamid 6.6